Hand pollination for improving productivity and quality of watermelon - Vennila, Soorya; Ramesh, K (Indian Horticulture, 2020)
Hand pollination is promising in the places where inadequate population of pollinators and scarce water availability for irrigation are experienced. It can improve the socio-economic conditions of the farmers by taking care of the yield. Inadequate pollination is one of the main reasons for the low productivity of many fruit and nut crops. Given the central role of pollination in orchard productivity, pollination management must become as important as other horticultural practices if economic returns and agricultural competitiveness is to be enhanced. Hand pollination gives better yield, promotes rural employability and thus provides livelihood security to marginal farmers.